The Overview of Food Technology to Process Soy Protein Isolate and Its Application toward Food Industry - Astawan, Made; Prayudani, Ayu P.G (World Nutrition Journal, 2020)
Soy protein isolate (SPI) is the purest form of protein from soybean with minimum protein content of 90%. Due to its high protein content, SPI is commonly used in food processing for improving the quality of food products, including infant formula. The use of SPI in infant formula is mainly designed for infant who cannot tolerate cow’s milk-based formula. This report reviews the benefit of using SPI in soy-based infant formula rather than soymilk from whole soybean itself. It will also review the technology of soy protein isolation which can result SPI for high quality infant formula, including the reducing of unfavourable ingredients which will ensure the safety of soy protein-based infant formula.